Diabetes mellitus among HIV patients on ART at Woldia comprehensive specialized hospital, Northeast Ethiopia - Alene Geteneh; Seada Muhammed; Selamyhun Tadesse; Aragaw Tesfaye; Solomon Rega; Sirak Biset; Mulugeta Kiros (Scientific Reports)
Abstract Diabetes mellitus (DM) is an emerging comorbidity among people living with HIV receiving antiretroviral therapy (ART), potentially impacting treatment outcomes, including virologic failure. Identifying key determinants of DM in this population is crucial for improving patient care. A hospital-based cross-sectional study was conducted from January 01 to May 30, 2024 at Woldia Comprehensive Specialized Hospital, Ethiopia. A total of 253 HIV patients on ART for at least six months were randomly selected. Data were collected via structured questionnaires, clinical measurements, and medical record reviews. DM was diagnosed on the basis of a fasting blood glucose level ≥ 126 mg/dl or random plasma glucose level ≥ 200 mg/dl. Logistic regression models were employed to identify factors associated with DM, reporting adjusted odds ratios (AORs) with 95% confidence intervals (CIs). Statistical significance was set at p < 0.05. The prevalence of DM among the study participants was 9.9%. Compared with female patients, male patients had a significantly greater risk of developing DM (AOR = 4.29, 95% CI = 1.079–17.04). A family history of DM was associated with a nearly 11-fold increased risk (AOR = 10.65, 95% CI = 2.82–40.20). Overweight individuals (BMI > 25 kg/m²) had a nearly sixfold-fold greater risk of DM (AOR = 5.95, 95% CI = 1.56–22.65). Additionally, ART interruption and restarting of ART were significantly associated with increased DM risk (AOR = 6.11, 95% CI = 1.88–19.84). Approximately one in ten HIV patients on ART had DM. The significant factors included male sex, family history of DM, overweight status, and ART interruption. These findings highlight the need for routine metabolic screening, targeted interventions and continuous monitoring to mitigate DM risk and optimize HIV care.